EVALUASI KEBIJAKAN DISTRIBUSI PROGRAM BERAS SEJAHTERA DI DESA TOLOK 1 KECAMATAN TOMPASO KABUPATEN MINAHASA - WOWILING, VANDA; POSUMAH, JOHNNY HANNY; LONDA, VERY (Sam Ratulangi University, 2018)
abstract: Rastra program is one of the government's strategy to eradicate poverty, especially in fulfilling theneed of food for poor people which aims to help reduce the burden of Poor Household in fulfilling basic foodneeds as one of the basic rights of society. But in the implementation of this program often experience variousproblems, rastra not until channeled into the hands of RTS-PM rastra, not right target, not appropriate price,not timely, not appropriate quality. It is therefore necessary to evaluate the implementation of the program tosee if the implementation has been done successfully in accordance with the general guidelines asappropriate. Program evaluation is to measure program's achievement, that is measure the effect of aprogram on the goals to be achieved and determine the success rate of the program of the activities made andto contribute the thinking to the decision maker about a program to improve the program to come. Based onthe results of the research, the achievement of the indicator according to William Dunn is the effectiveness,efficiency, adequacy, equity, responsiveness, and accuracy as a measure of successful implementation on theperformance of the program, indicating that the implementation of distribution of Rastra Program Year 2017in Tolok 1 Village is still not running maximally.Keyword : Evaluation, Policy, Distribution, Prosperous Rice